2010
DOI: 10.1002/er.1718
|View full text |Cite
|
Sign up to set email alerts
|

Development of methanol-fueled low-temperature solid oxide fuel cells

Abstract: SUMMARYLow-temperature solid oxide fuel cell (SOFC, 300-6001C) technology fueled by methanol possessing significant importance and application in polygenerations has been developed. Thermodynamic analysis of methanol gasphase compositions and carbon formation indicates that direct operation on methanol between 450 and 6001C may result in significant carbon deposition. A water steam/methanol ratio of 1/1 can completely suppress carbon formation in the same time enrich H 2 production composition. Fuel cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 20 publications
2
44
0
1
Order By: Relevance
“…[60] The direct utilization of liquid fuels, on the other hand, by internal reforming would make the LT-SOFC system, simple and cost-effective. [63] Similarly, Y. Jiang et al reported a high power density of 600 mW/cm 2 at 650°C for an SOFC (Ni-YSZ anode j YSZ electrolyte j LSM-YSZ cathode) operating on methanol as fuel. Several attempts were made to directly utilize liquid fuels for LT-SOFCs by internal reforming.…”
Section: Status Of Liquid-fed Lt-sofcsmentioning
confidence: 96%
See 1 more Smart Citation
“…[60] The direct utilization of liquid fuels, on the other hand, by internal reforming would make the LT-SOFC system, simple and cost-effective. [63] Similarly, Y. Jiang et al reported a high power density of 600 mW/cm 2 at 650°C for an SOFC (Ni-YSZ anode j YSZ electrolyte j LSM-YSZ cathode) operating on methanol as fuel. Several attempts were made to directly utilize liquid fuels for LT-SOFCs by internal reforming.…”
Section: Status Of Liquid-fed Lt-sofcsmentioning
confidence: 96%
“…LiÀ NiÀ CuÀ ZnO anode j SDC-Li 2 CO 3 À Na 2 CO 3 electrolyte j LiÀ NiÀ CuÀ ZnO cathode [63] 600 methanol/ H 2 O 603 Steam reforming…”
Section: Fuel Utilization Strategymentioning
confidence: 99%
“…These composites include one classical ceria‐based electrolyte (e.g. CGO‐gadolinia doped ceria) and one mixture of alkali metal carbonates (frequently Li and Na carbonates) as second phase 8–19.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ZnGa 2 O 4 structure becomes promising material in wide range optical device applications [14][15][16]. Because of it's higher band gap than that of ZnO, it is possible for ZnGa 2 O 4 to function above 300 C. Therefore, ZnGa 2 O 4 might be useful in the low temperature fuel cell electrolyte (LTFCE) materials similar to SDC (samarium doped ceria) [17]. There are also some examples for wide band gap gallete based semiconductors used in LTFCE; i.e., the study on b-Ga 2 O 3 has shown that defect formation dependent conductivity begins at around 700 K due to surface/lattice oxygen reduction in H 2 [18].…”
Section: Introductionmentioning
confidence: 99%